THE EFFECT OF TRICHODERMA HARIZANUM FUNGUS USAGE AS BIO- FERTILIZER ON TOMATO SEEDLING GROWTH - & et al., AL-Surhanee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
In this study the Trichoderma harizanum was to know the possibility of using it as bio fertilizer instead of chemical fertilizers, where it was added to planted soil with tomato seeds in the following proportions:  adding the fungus with concentration 1%,2% - adding the fungus with NPK fertilizer as mixture with percentage 1:1,2:2 -adding NPK fertilizer alone with concentration  1%,2% , after three weeks, the results of plantation showed significant increase for all examined characteristics in each  : germination ratio , seedling length ,dry and wet weight  in the case of usage of Trichoderma Hariznum fungus only in different concentrations , the best result was at concentration 2% comparing to control sample , where  the increase percentages were 1.05%,5.14%,.75%.3.9% respectively , as there was a significant increase for all examined characteristics in case of usage of fungus and fertilizer together ,also in case of usage of fertilizer only. These results indicated that the fungus has positive role in supporting and feeding the plant ,and  increasing the growth and production of crop, the results recommends using of bio fertilizer  as safety alternative  for human health , which doesn’t cause any pollution , it also recommends  the adaptation of  complete fertilization , and conducting more researches in bio-fertilizers field